1980
DOI: 10.1172/jci109867
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Differentiation and Immunoregulatory T Cell Function in Human Cord Blood Lymphocytes

Abstract: A B S T R A C T The functional maturity of T and B lymphocyte populations from human newborns was evaluated using a reverse hemolytic plaque assay to detect immunoglobulin-secreting cells generated in in vitro cultures stimulated with pokeweed mitogen (PWM), a T cell-dependent polyclonal activator, and the Epstein-Barr virus (EBV), a T cell-independent B cell activator. Cord blood lymphocytes failed to produce immunoglobulin in response to PWM, but did respond with immunoglobulin synthesis to stimulation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(47 citation statements)
references
References 20 publications
3
43
1
Order By: Relevance
“…These studies did not exclude the possibility that suppression might develop primarily as a result of the mitogen activation of the newborn cells. Indeed, Tosato et al (25) finding that newborn T cells did not suppress adult lymphocyte responses to Epstein-Barr virus unless a mitogen was added, and our own observation of relatively low numbers of cells with the OKT 8+ suppressor phenotype in newborn blood (8) are consistent with the view that newborn T cells are not intrinsically suppressive, though they may become so as a result of mitogen activation. Lawler et 01.…”
Section: Response Of Human Newborn Lymphocytes Tosupporting
confidence: 88%
“…These studies did not exclude the possibility that suppression might develop primarily as a result of the mitogen activation of the newborn cells. Indeed, Tosato et al (25) finding that newborn T cells did not suppress adult lymphocyte responses to Epstein-Barr virus unless a mitogen was added, and our own observation of relatively low numbers of cells with the OKT 8+ suppressor phenotype in newborn blood (8) are consistent with the view that newborn T cells are not intrinsically suppressive, though they may become so as a result of mitogen activation. Lawler et 01.…”
Section: Response Of Human Newborn Lymphocytes Tosupporting
confidence: 88%
“…Specific defects include delayed maturation of B cells into antibody-producing cells (9)(10)(11)(12), deficient stimulation of T-cell maturation (1 3-15), and delayed induction of hematopoietic progenitor cell cycling (16). The clinical deficiencies resulting from these immature cellular processes include blunted synthesis of specific IgG (12,17,18) and delayed up-regulation of neutrophil production (19,20).…”
mentioning
confidence: 99%
“…Furthermore, it is clear that although the precise cascade of events leading to IgE production induced by IL-4 in vivo still remains to be determined, the frequency of successful IgE production in vitro by PBMC of patients with CVI is much lower than that by PBMC of healthy donors (2/8 versus 7/8), It remains to be clarified why PBMC of healthy donor 6 failed to produce IgE, but recent studies in our laboratory have indicated the PBMC of a small proportion of healthy donors do not produce IgE under the present culture conditions (Chretien et al, 1990), It has been shown that B cells of patients with CVI behave functionally like immature cord blood B cells (de Gast et al, 1980;Tosato e;Platts-Millse/a/,, 1981;Perreirae/a/,, 1982;Haber era/,, 1983;Brenner era/,, 1984;Mayer era/,, 1984), Stimulation of B cells of patients with CVI by EBV, PWM or supernatants of activated T cells results, as with cord blood B cells, predominantly in secretion of IgM and no or very low levels of IgA and IgG, However, we have found that cord blood cells from 8/8 donors produced IgE in the presence of IL-4, indicating that cord blood B cells and B cells of CVI patients differ in their capacity to produce IgE in response to unpublished). Therefore, B cells from patients with CVI cannot be compared functionally with cord blood B cells.…”
Section: Discussionmentioning
confidence: 86%